Fiscal risks : sources, disclosure, and management / Aliona Cebotari ... [et al.]. - Cebotari, Aliona. (International Monetary Fund, 2009)
This paper analyzes the main sources of fiscal risks, including from unexpected changes in macroeconomic variables and banking crises, which can have major consequences for countries' fiscal and public debt sustainability. It builds on an overview of existing practices in a wide range of countries to provide practical suggestions on how to promote disclosure of such risks and on risk mitigation and management. It also includes an example of a possible statement of fiscal risks. The paper was written in response to requests from IMF member countries for advice on this subject. .--Publisher's description.